2005
DOI: 10.1074/jbc.m411256200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Class of Target Genes and a Novel Type of Binding Sequence of Heat Shock Transcription Factor in Saccharomyces cerevisiae

Abstract: In response to hyperthermia, heat shock transcription factor (HSF) activates transcription of a set of genes encoding heat shock proteins (HSPs). The promoter regions of HSP genes contain the HSF binding sequence called the heat shock element (HSE), which consists of contiguous inverted repeats of the sequence 5-nGAAn-3 (where n is any nucleotide). We have constructed an hsf1 mutant of Saccharomyces cerevisiae and analyzed genome-wide changes in heat shock response in the mutant cells. The results have reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
177
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 62 publications
1
177
0
1
Order By: Relevance
“…It has beeen reported that the HSE and its binding protein heat shock transcription factor are highly conserved from yeast to humans. [19][20][21] It is well known that heat shock and hydrogen peroxide induces catalase gene expression in Aspergilli 5,[22][23][24] and other species, [6][7][8]25) and that each catalase gene promoter has regulatory element for stress response. But the regulatory elements are different in species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has beeen reported that the HSE and its binding protein heat shock transcription factor are highly conserved from yeast to humans. [19][20][21] It is well known that heat shock and hydrogen peroxide induces catalase gene expression in Aspergilli 5,[22][23][24] and other species, [6][7][8]25) and that each catalase gene promoter has regulatory element for stress response. But the regulatory elements are different in species.…”
Section: Discussionmentioning
confidence: 99%
“…NS indicates nonspecific competitor. Either 10 pmol (lanes 3,6,9,12,15,20,23,26,29, and 32), 5 pmol (lanes 4, 7, 10, 13, 16, 21, 24, 27, and 30), or 1 pmol (lanes 5,8,11,14,17,22,25,28, and 31) of the competitors were added. SB and FP indicate the shifted band and the free probe, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…ScSFL1 encodes a negative regulator of pseudohyphal growth and invasion [31] and was isolated based on its ability to suppress flocculation defects in yeast [32]. ScSfl1p carries a putative heat shock factor (HSF)-type DNA binding domain and binds in vitro to a GAA triplet motif [33] characteristic of heat shock elements (HSEs) [34], while exerting its negative regulation through the recruitment of the Ssn6p-Tup1p corepressor complex [35]. ScSfl1p has dual activator/repressor functions, acting as a transcriptional repressor of flocculation-related genes and as an activator of stress-responsive genes [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…A genome-wide ScHsf1 binding analysis indicates that ScHsf1 binds to the 5Ј-upstream regions of a set of genes that participate in a broad range of biological functions (29). The heat shock-induced transcription of many of these genes is inhibited in cells containing an Schsf1 mutation, although several of the target genes lack an apparent HSE in their promoter regions (20). In the present study, we identified the ScHsf1-binding sequences in most of the target genes examined and showed that ScHsf1 binds to and activates transcription via HSEs that diverge from the canonical sequence.…”
mentioning
confidence: 99%
“…The differently arranged nGAAn units are classified as follows: the perfect-type HSE consists of continuous inverted repeats of the unit (nTTCnnGAAnnTTCn), the gap-type contains one gap between the units (nTTCnnGAAn(5 bp)nGAAn), and the step-type contains two gaps (nTTCn(5 bp)nTTCn(5 bp)nTTCn) (20). Various ScHsf1 domains are involved in HSE architecture-specific transcription.…”
mentioning
confidence: 99%